2013
DOI: 10.1016/j.jpeds.2012.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes of Newborns with Perinatal Acidemia Who are Not Eligible for Systemic Hypothermia Therapy

Abstract: Objective To determine short-term outcomes of infants who had perinatal acidemia and were evaluated for hypothermia therapy but did not qualify based on a standardized neurologic examination. Study design Retrospective, single-site cohort study of inborn infants of ≥36 weeks gestation who had perinatal acidemia from October 2005-September 2008 and had a standardized neurologic examination performed by a certified neonatologist to assess eligibility for hypothermia therapy. An abnormal short-term nursery outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 26 publications
6
61
0
Order By: Relevance
“…This group of neonates with mild HIE are poorly characterized, and recent evidence suggests that up to 20% can have abnormal short-term outcomes. 47 Unfortunately, data on multiple organ injury (eg, creatinine, liver enzymes) in these neonates with mild HIE were not evaluated. Findings in the neonates with encephalopathy support the search for biomarkers in addition to the neurological examination to better stratify subgroups that might benefit from neuroprotective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This group of neonates with mild HIE are poorly characterized, and recent evidence suggests that up to 20% can have abnormal short-term outcomes. 47 Unfortunately, data on multiple organ injury (eg, creatinine, liver enzymes) in these neonates with mild HIE were not evaluated. Findings in the neonates with encephalopathy support the search for biomarkers in addition to the neurological examination to better stratify subgroups that might benefit from neuroprotective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by DuPont et al found that 20% of infants with perinatal acidemia and a neurologic examination revealing only mild encephalopathy had abnormal short-term outcomes including feeding difficulties, abnormal MRI, seizures, abnormal neurologic exam at discharge or death. 19 An ongoing observational study may provide further information regarding the natural history and outcomes of children with mild HIE (NCT01747863).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that HRV is negatively associated with EEG grade of HIE severity and demonstrated significant differences in HRV between mild and moderate EEG grades and also between mild and severe grades. This is an important finding as it is sometimes difficult to distinguish between mild and moderate grades of encephalopathy using currently available clinical markers (13). Neonates with severe HIE, on the other hand, are generally easier to identify clinically.…”
Section: Prediction Of Neurodevelopmental Outcomementioning
confidence: 99%